2012
DOI: 10.1682/jrrd.2011.07.0127
|View full text |Cite
|
Sign up to set email alerts
|

Center of mass acceleration feedback control of functional neuromuscular stimulation for standing in presence of internal postural perturbations

Abstract: This study determined the feasibility and performance of center of mass (COM) acceleration feedback control of a neuroprosthesis utilizing functional neuromuscular stimulation (FNS) to restore standing balance to a single subject paralyzed by a motor and sensory complete, thoracic-level spinal cord injury (SCI). An artificial neural network (ANN) was created to map gain-modulated changes in total body COM acceleration estimated from body-mounted sensors to optimal changes in stimulation required to maintain st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…The simulation study described in Nataraj et al determined that the typical noise and tracking errors reported for such sensors were within acceptable boundaries to still resolve postural positions with sufficient accuracy for effective feedback control of neuroprosthetic standing [30]. While the required precision of the sensors was not assessed in this study, the previous utilization of such sensors with our customized implantable stimulator for feedback control of neuroprosthetic standing suggests potential feasibility for live-subject implementation for setpoint control as well [2][3]. The model-based study presented here has some intrinsic limitations.…”
Section: Shouldermentioning
confidence: 79%
See 2 more Smart Citations
“…The simulation study described in Nataraj et al determined that the typical noise and tracking errors reported for such sensors were within acceptable boundaries to still resolve postural positions with sufficient accuracy for effective feedback control of neuroprosthetic standing [30]. While the required precision of the sensors was not assessed in this study, the previous utilization of such sensors with our customized implantable stimulator for feedback control of neuroprosthetic standing suggests potential feasibility for live-subject implementation for setpoint control as well [2][3]. The model-based study presented here has some intrinsic limitations.…”
Section: Shouldermentioning
confidence: 79%
“…Our previous studies investigated use of CoM for feedback control based on 3D acceleration of CoM for the express purpose of disturbance rejection about the nominal posture setpoint [2][3]26]. Stimulation levels were modulated to respond to unanticipated, dynamic changes occurring only while standing at that nominal position.…”
Section: Shouldermentioning
confidence: 99%
See 1 more Smart Citation
“…Device actuation may be more passive as with AFO assistance from spring-loads being applied proportional to displacements ala Hooke's law (F = -kx) and mediated through well-executed clutching [28]. Device actuation may be more active such as functional neuromuscular stimulation (FNS) to activated paralyzed musculature and restore standing balance capabilities [29] or electromotor actuation to restore walking [30] following spinal cord injury (SCI).…”
Section: Biomimetic Prosthetics 52mentioning
confidence: 99%
“…To this end, our group has developed control systems that modulate stimulation to muscles spanning the ankles, knees, hips, and trunk for comprehensive standing balance. We have demonstrated that feedback control can notably reduce the upper extremity (UE) loading required to stabilize against postural perturbations up to 50% in computer simulation [8][9][10] and 27-33% under live-subject conditions [12,13] compared to constant muscle excitation levels. While the procedures implemented to heuristically tune the feedback gains for these controllers were appropriate for initial evaluations, their repeated implementation would be clinically inconvenient by requiring substantial subject time and effort for periodic re-tuning over long-term usage.…”
Section: Introductionmentioning
confidence: 99%